Visualizing and controlling vibrational wave packets of single molecules - Brinks, Daan (2010)
The active steering of the pathways taken by chemical reactions and the optimization of energy conversion processes provide striking examples of the coherent control of quantum interference through the use of shaped laser pulses. Experimentally, coherence is usually established by synchronizing a subset of molecules in an ensemble with ultra-short laser pulses. But in complex systems where even chemically identical molecules exist with different conformations and in diverse environments, the synchronized subset will have an intrinsic inhomogeneity that limits the degree of coherent control that can be achieved. A naturaland, indeed, the ultimatesolution to overcoming intrinsic inhomogeneities is the investigation of the behaviour of one molecule at a time. The single-molecule approach has provided useful insights into phenomena as diverse as biomolecular interactions, cellular processes and the dynamics of supercooled liquids and conjugated polymers. Coherent state preparation of single molecules has so far been restricted to cryogenic conditions, whereas at room temperature only incoherent vibrational relaxation pathways have been probed. Here we report the observation and manipulation of vibrational wave-packet interference in individual molecules at ambient conditions. We show that adapting the time and phase distribution of the optical excitation field to the dynamics of each molecule results in a high degree of control, and expect that the approach can be extended to achieve single-molecule coherent control in other complex inhomogeneous systems.